Silica gel: an improved support for the solid-phase phosphotriester synthesis of oligonucleotides. - Kohli, V (1982)
The phosphotriester method for the stepwise synthesis of deoxyoligonucleotides has been employed using HPLC-grade silica gel (Porasil B) as the solid support. The procedure results in a convenient flow-through system for the synthesis of oligomers where all the reaction steps including the zinc bromide method of detritylation are compatible with the selected support. Deoxyoligonucleotides of 25-30 nucleotides in length can be synthesized in high yields utilising stable phosphotriester intermediates. Ease of handling of the solid support allows convenient synthesis of mixed oligonucleotide sequences.